Utilização do tanino como preservante natural da madeira de Acacia mearnsii e sua toxidez ao fungo apodrecedor Pycnoporus sanguineus - Silveira, Amanda Grassmann da (2015)
The present study aimed to evaluate the use of tannin as natural preservative of Acacia mearnsii and its toxicity to the wood-decay fungus Pycnoporus sanguineus. It was divided in two main stages: the first was to find the best way to work with the tannic extract, developing methodologies and concentrations to allow better check of the product toxicity. These were employed through experiments in culture environment, also known as fungitoxic tests, assessed through the index of mycelial growth. In the second step, through the accelerated test, wood proof bodies were treated with different doses of tannin, drawn up in accordance with the results found in the previous step. The biodeterioration of the exposed material was evaluated based on the mass loss, chemical analysis and hardness testing. The results indicated that the extractive tannin is toxic to the fungi development, showing that the higher the concentration of tannin in the environment, the greater was their inhibitory power in mycelial growth. To evaluate the effect on wood preservative in relation to mass loss were used two concentrations of tannin, 5 and 10%, and its performance compared with the witnesses: upper, treated with mixture and lower BAC without treatment with natural resistance. The natural resistance evaluated by mass loss proved to be moderately resistant, whereas when treated with both concentrations of the extract and mixture CCB passed to very resistant .On the evaluation of chemical components, the components most affected by decay were the lignin and cellulose, being proven through the results that the treatment performed with the tannin to 10% preserved in the same way that the industrial product. Rockwell hardness presented results that prove the efficiency of tannins as wood preservative, showing the similar performance of tannin when compared to the chemical mixture.